What Goes Along with the Energy Ladder? Regression Analysis and Crisp-Set Qualitative Comparative Analysis - Matsubara, Fumihiko (International Journal of Energy Economics and Policy, 2025)
The study reveals that, while economic variables, such as income, remain central to explaining clean energy adoption in the selected 20 African countries, other non-economic elements, like access to infrastructure and social demographics, can exert notable influence under certain circumstances. To enable comparison, two analyses were employed: regression analysis and crisp-set qualitative comparative analysis (cs-QCS). The trend findings show higher adoption rates of clean cooking fuels in West and Central Africa, particularly under certain socioeconomic and infrastructure conditions (high rates of female household heads and access to electricity). Conversely, East Africa has made limited progress due to specific socioeconomic and infrastructure constraints (low rates of improved water and access to electricity). These results reinforce the primary relevance of the Energy Ladder theory for African nations but also indicate that certain combinations of social factors modulate clean energy utilization. Thus, the study highlights the need for a more nuanced understanding of how economic and non-economic determinants interact and shape household fuel choices across diverse regional settings in Africa, which goes beyond energy stacking.